Editorial - Pacheco-Romero, José (2016)
In the last quarter of 2015, the Regional Council for Science, Technology and Technological Innovation - CONCYTEC of Peru called the Peruvian scientific journals indexed to apply for the National Fund for Scientific, Technological Development and Technological Innovation - CONDECYT / Cienciactiva for support economic intended to publish, over a period of two years, a greater number of quality goods with the aim of indexing importance databases, including Scopus and web of Science. The Peruvian Journal of Gynecology and Obstetrics (RPGO) has earned this award strengthens and will raise its editorial quality. The Editorial Committee of the RPGO is very proud to have obtained such important support that will eventually encourage him to publish original articles and other types of scientific articles in English. Beginning this new era, in this issue the editorial present original articles and two special interest in English and Spanish is published. And an article is published in Portuguese. The RPGO invites all its readers and friends to send their work and related to obstetrics, gynecology and human reproduction in English, Spanish or Portuguese articles, following the instructions in the Information for Authors of the journal.